Evaluation of active neutrophil elastase in sputum of bronchiectasis and cystic fibrosis patients: A comparison among different techniques. (December 2019) - Oriano, Martina; Terranova, Leonardo; Sotgiu, Giovanni; Saderi, Laura; Bellofiore, Angela; Retucci, Mariangela; Marotta, Cinzia; Gramegna, Andrea; Miglietta, Daniela; Carnini, Chiara; Marchisio, Paola; Chalmers, James D.; et al.
Abstract: Neutrophil elastase (NE) is a crucial marker of neutrophilic inflammation. We aimed to compare different techniques to detect active NE in sputum samples of 50 Bronchiectasis (BE) and 50 Cystic Fibrosis (CF) patients. Three methods including a ProteaseTag® Active NE Immunoassay (ELISA) and two enzymatic digestion assays (chromogenic –CS- and fluorogenic –FS- substrate) were compared. Results of active NE were also correlated with clinical data. The three methods provided statistically different values for NE activity in the same sputum samples in both cohorts. In the BE cohort, the highest correlations between NE activity and Bronchiectasis Severity Index (rho = 0.40, P < 0.0001), sputum purulence (AUC = 0.79), and chronic infections due to any pathogen (AUC = 0.76) and P. aeruginosa (AUC = 0.80) were found when NE was measured through the activity-based immunoassay. In the CF cohort, the highest correlations between NE activity and sputum quantity (rho = 0.71) and FEV1% (rho = 0.42, P = 0.03) were observed when the FS method was used, while similar correlations with chronic P. aeruginosa infection were identified with the FS and ELISA methods. NE activity in sputum correlates with clinical variables in both diseases. However, different methods to evaluate active NE in sputum lead to significantly different results, also in terms of correlation with clinical data.